Peningkatan Kemampuan Menulis Teks Berita Berbantuan Peta Konsep Siswa Kelas VIII.1 SMP Negeri 20 Padang - Diastiti, Liana; Atmazaki, Atmazaki; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This study aimed to describe the process and the resulting increase in the ability to write news VIII.1 grade students of SMP Negeri 20 Padang through concept maps techniques. The application of the concept map technique is expected to provide benefits to enhance the spirit of the students in writing news properly because of technical inquiry prefers a meaningful process rather than results. This research is action research, the research subjects were students of SMP Negeri 20 VIII.1 class Padang totaling 37 people, classroom action research is descriptive method research design class action include: (1) planning, (2) implementation, (3) observation, and (4) reflection. The data in this study in the form of a written test results of students, observation sheets, field notes and students' questionnaire responses. Analyzing the data obtained by: (1) conduct preliminary observations on the ability to write news, (2) perform a test write news, and (3) complete a questionnaire. Furthermore, the data processed by classifying the qualitative and quantitative data and provide the results of student test scores. Based on the results of data analysis it can be concluded that the technique of concept maps in teaching writing can enhance students' ability to write a story in class VIII.1 SMP 20 Padang with more than enough qualifications.